Ajuba functions as a co-activator of C/EBPβ to induce expression of PPARγ and C/EBPα during adipogenesis. (1st January 2022) - Yan, Han; Li, Qi; Li, Mengying; Zou, Xiuqun; Bai, Ningning; Yu, Zichao; Zhang, Jie; Zhang, Dan; Zhang, Qun; Wang, Jiamin; Jia, Hao; Wu, Yingjie; et al.
Abstract: Adipogenesis is regulated by a complicated network of transcription factors among which PPARγ and C/EBP family members are the major regulators. During adipogenesis, C/EBPβ is induced early and then transactivates PPARγ and C/EBPα, which cooperatively induce genes whose expressions give rise to the mature adipocyte phenotype. Identifying the factors that influence the expression and activity of C/EBPβ should provide additional insight into the mechanisms regulating adipogenesis. Here, we demonstrate that depletion of Ajuba in 3T3-L1 cells significantly decreases mRNA and protein levels of PPARγ and C/EBPα and impairs adipocyte differentiation, while overexpression increases expression of these genes and promotes adipocyte differentiation. Moreover, restoration of C/EBPα or PPARγ expression in Ajuba-deficient 3T3-L1 cells improves the impaired lipid accumulation. Mechanistically, Ajuba interacts with C/EBPβ and recruits CBP to facilitate the binding of C/EBPβ to the promoter of PPARγ and C/EBPα, resulting in increased H3 histone acetylation and target gene expression. Collectively, these data indicate that Ajuba functions as a co-activator of C/EBPβ, and may be an important therapeutic target for combating obesity-related diseases. Highlights: Ajuba promotes expression of PPARγ and C/EBPα during adipogenesis. Ajuba interacts with C/EBPβ and enhances its transactivity. Ajuba recruits CBP to increase the enrichment of C/EBPβ on the promoter of PPARγ and C/EBPα.